Stress level experienced by participants in realistic simulation: a systematic review - Guilherme da Costa Brasil; Lucas Tomaz Benigno Lima; Elaine Carvalho Cunha; Flávia Oliveira de Almeida Marques da Cruz; Laiane Medeiros Ribeiro (Associação Brasileira de Enfermagem, 2021)
ABSTRACT Objectives: to identify the available evidence regarding stress levels experienced by participants in education based on a realistic simulation. Methods: systematic review that included randomized clinic trials on electronic databases: Cumulative Index to Nursing and Allied Health Literature, Cochrane Library, Latin-American and Caribbean Literature in Health Sciences, LIVIVO, PubMed, Scopus, and Web of Science. The additional search was performed on Google Scholar and OpenGrey. All searches occurred on September 24, 2020. The methodologic quality of the results was evaluated by the Cochrane Collaboration Risk of Bias Tool. Results: eighteen studies were included, which evaluated the participants' stress using physiologic, self-reported measures, or the combination of both. Stress as experienced in a high level in simulated scenarios. Conclusions: evidence of the study included in this systematic review suggest that stress is experienced in a high level in simulated scenarios.